First Report of a Successful Pregnancy in an Everolimus‐Treated Heart‐Transplanted Patient: Neonatal Disappearance of Immunosuppressive Drugs. Issue 4 (10th November 2015) - Fiocchi, R.; D'Elia, E.; Vittori, C.; Sebastiani, R.; Strobelt, N.; Eleftheriou, G.; Introna, M.; Freddi, C.; Crippa, A.
Abstract : The use of everolimus (EVL) as primary immunosuppression is steadily increasing in heart transplantation (HTx) patients. Limited data currently exist in kidney transplantation, but there is no report of EVL use during pregnancy after HTx and its pharmacokinetics in the newborn. We report a case of an unplanned pregnancy discovered at 21 weeks of gestation in a female HTx patient aged 40 years treated with EVL and cyclosporine (CyA). Because pregnancy was advanced, immunosuppression therapy was left unchanged. At 36 weeks, a healthy infant was delivered. At birth, CyA blood levels were lower in the neonate, but EVL concentrations in maternal and neonatal umbilical blood were similar. Amniotic fluid concentrations were undetectable for both drugs. In the newborn, EVL was measurable at 5 days after birth, whereas CyA disappeared within 2 days. Cord blood displayed a normal count of B and T cells and CD4, CD8 and natural killer cell populations. At birth, both mother and newborn displayed the same blood levels of EVL; therefore, a filter effect of the placenta may be hypothesized for CyA but not for EVL. No immediate complications were observed with this pregnancy. Abstract : The authors present the first successful pregnancy in a heart transplant patient treated with everolimus and cyclosporine and show that the two immunosuppressive agents may have a different pharmacokinetic profile in the newborn.